Chemical compositions of the essential oil of Pinus kwangtungensis Chun ex Tsiang from Vietnam - Thai, Tran Huy; Tuyet Hong, Phung Thi (Academia Journal of Biology, 2014)
Pinus kwangtungensis Chun ex Tsiang (Pinaceae) distributes in the Caobang, Hagiang, Hoabinh and Sonla provinces at 900-1400m alt.. The yield of the essential oil from leaves was 0.03 percent by air-dry material. This essential oil was analysed by GC/MS and 31 constituents of essential oil were identified. The main constituents of this oil were: a-pinen (16.41%), b-caryophyllen (14.50%), d-cadinen (8.09%), a-cadinol (7.59%), bicyclo [4.4.0] dec-1-en, 2-isopropyl-5-methyl-8-methylen (6.77%) and 1-limonen (6.65%).